A cryptography‐based protocol against packet dropping and message tampering attacks on mobile ad hoc networks1. Issue 2 (22nd February 2013) - Obaidat, Mohammad S.; Woungang, Isaac; Dhurandher, Sanjay Kumar; Koo, Vincent
ABSTRACT In mobile ad hoc networks (MANETs), nodes are mobile in nature, but at the same time, they are assumed to rely on each other to relay their traffic even in case the wireless transmission medium is out of range. This requirement poses a serious challenge when malicious nodes are present in the MANET and may contribute to the routing operations, either by tampering the data packets or dropping them. This paper addresses this particular type of wormhole attacks, by introducing an enhancement (the so‐called E‐HSAM) to a recently proposed ad hoc on‐demand distance vector‐based protocol for preventing against such attacks in MANETs (the so‐called highly secured approach against attacks on MANETs (HSAM)). Our contributions are twofold: (i) a simulation study of the HSAM protocol is provided for the first time, and (ii) the Advanced Encryption Standard (AES) is introduced in the route selection phase of E‐HSAM (yielding our so‐called E‐HSAM‐AES scheme) to strengthen the integrity of the data while securing the potential routes chosen for data transfer from source to destination nodes. Simulation results are presented, showing the superiority of E‐HSAM‐AES over E‐HSAM and HSAM in terms of packet delivery ratio and broken link detected during data transmission, chosen as performance metrics. Copyright © 2013 John Wiley & Sons, Ltd.